Power Spectral Density Estimation and THD of Motor Line Currents of AZSPWM Based DTC of Induction Motor Drive - Lakshmi, V. Anantha; G, Satheesh.; Reddy, T. Bramhananda (International Journal of Engineering and Technology, 2018)
Estimating the power distribution over a given frequency range and the total harmonic distortion of the line currents of the AZSPWM based induction motor drive is discussed in this paper. Applying a spectrum analysis on the motor line currents and inspecting the spectrum amplitudes at different switching frequencies for abnormality is a well-known procedure for acoustic noise detection and diagnosis. Among the spectrum analysis techniques for acoustic noise detection, the Fast Fourier Transform (FFT) is the most widely used technique. There are other spectrum techniques, which are based on the power spectral density (PSD) estimates. AZSPWM based DTC of induction motor currents are estimated for the power spectral densities. The harmonic spectra and the power spectral density estimates of all AZSPWM family are validated through the MATLAB/ simulink environment.